The importance of financial literacy among degree student : A case study in Academy of Contemporary Islamic Studies, UiTM Shah Alam / In Am Nabila Mohd Hashim - Mohd Hashim, In Am Nabila (Academy of Contemporary Islamic Studies, 2018)
Financial literacy defined merely as a combination of awareness, knowledge, skills, attitude, and behaviour necessary to make an individual financially well-off. International research works show that among the third world countries like Malaysia, the rate of financial literacy is still relatively low. The primary purpose of conducting this study was to gauge if the Social Studies majors are financially literate since they have the background on economics-related courses and to find out who influences them in financial management. Using the quantitative-survey research, the researchers made use of purposive sampling among eighty (80) respondents Academy of Contemporary Islamic Studies students. Based on the findings of the study, for the influences, the respondents acknowledged their parents as their primary influencers. Therefore, the research shows that the respondent's demographic profile didn't affect his/her financial literacy. Students were influenced by parents regarding financial matters at an early age and exposure to economics-related subjects may have increased financial literacy.